life course and development of personality of the great Chinese writer Pu Songling (Journal of Oriental Studies, 2016)
this article describes the stages of life of the Chinese writer Pu songling, the formation of his identity as a writer and a man. the importance of his father in the life of the writer was shown, briefly discussed the ideas that influenced the development of psycho-social and intellectual growth of the writer, which subsequently reflected in the work of Pu songling and determined his unique literary style.
Keywords: education; confucianism; morality